PENGARUH KNOWLEDGE MANAGEMENT TERHADAP SUSTAINABILITY PERFORMANCE PRODUSEN SASIRANGAN DI KOTA BANJARMASIN DAN SEKITARNYA DENGAN GREEN INNOVATION SEBAGAI MEDIASI - Ferra Maryana; Ferli Erwansyah (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to give empirical evidence about Research result prove that knowledge management have effect on sustainability performance, and green innovation give mediation effect on the relationship between knowledge management and sustainability performance. This study uses a quantitative method that empirically tests the influence of knowledge management on the sustainability performance of sasirangan producers in Banjarmasin and its surroundings with green innovation as a mediator. The results of the study prove that knowledge management has an effect on sustainability performance, and green innovation can mediate the influence of knowledge management on sustainability performance.